Integrating spatial and social characteristics in the DPSIR framework for the sustainable management of river basins: case study of the Katari River Basin, Bolivia. Issue 1 (2nd January 2022) - Agramont, Afnan; van Cauwenbergh, Nora; van Griesven, Ann; Craps, Marc
ABSTRACT: The drivers–pressures–state–impact–responses (DPSIR) framework has been used widely to support environmental policy developments. However, we argue that DPSIR tends to oversimplify the complexity behind socio-ecological systems. Based on the Katari River Basin in Bolivia, we explore how the incorporation of spatial and social considerations may enhance DPSIR applications. The results reveal a spatial mismatch between driving forces/pressures and policy responses, and severe impacts on the vulnerable communities. Moreover, we also show that local levels tend to be neglected. The study concludes that integrating spatial and social characteristics in the DPSIR may result in valuable implications for river basin management practitioners.